Oral Manifestations of Eating Disorders - Neeta Misra; Anshul Mehra; Pradyuman Misra; Jaya Mehra (Wolters Kluwer Medknow Publications, 2010)
Eating disorders are potentially life-threatening disorders. In this article, we discuss the oral manifestations of eating disorders so as to enable dental practitioners to recognize the effects of eating disorders and to manage the patients with eating disorders.